The Rise of Tennis Tourism: Motivations, Experiences, and Economic Impact of Traveling Fans - BANCIU, Alexandru-Nicolae; TUDOR, Irina-Valentina; POPÎRLAN, Cristina (Journal of Environmental Management and Tourism, 2024)
This study explores the rise of tennis tourism, examining the motivations, experiences, and economic impact of fans who travel to attend tennis events. Through a mixed-methods approach combining quantitative survey and qualitative interviews, the study identifies three primary motivations for tennis tourism: the prestige of attending tournaments, emotional connections to prominent players, and the desire for cultural engagement in host cities. Results indicate that fans value not only the sport but also the unique atmosphere of the venues and opportunities for player interaction. Economic analysis reveals that tennis tourists contribute substantially to local economies through spending on accommodations, dining, and entertainment. This study highlights tennis tourism as a growing segment of the sports tourism industry and the unique characteristics of tennis fans, their travel patterns, and the economic implications of their participation in tennis events.